ATP-sensitive K+ channel-dependent regulation of glucagon release and electrical activity by glucose in wild-type and SUR1-/- mouse alpha-cells. - Gromada, J; Ma, X; Høy, M; Bokvist, K; Salehi, A; Berggren, P; Rorsman, P (2004)
Patch-clamp recordings and glucagon release measurements were combined to determine the role of plasma membrane ATP-sensitive K+ channels (KATP channels) in the control of glucagon secretion from mouse pancreatic alpha-cells. In wild-type mouse islets, glucose produced a concentration-dependent (half-maximal inhibitory concentration [IC50]=2.5 mmol/l) reduction of glucagon release. Maximum inhibition (approximately 50%) was attained at glucose concentrations >5 mmol/l. The sulfonylureas tolbutamide (100 micromol/l) and glibenclamide (100 nmol/l) inhibited glucagon secretion to the same extent as a maximally inhibitory concentration of glucose. In mice lacking functional KATP channels (SUR1-/-), glucagon secretion in the absence of glucose was lower than that observed in wild-type islets and both glucose (0-20 mmol/l) and the sulfonylureas failed to inhibit glucagon secretion. Membrane potential recordings revealed that alpha-cells generate action potentials in the absence of glucose. Addition of glucose depolarized the alpha-cell by approximately 7 mV and reduced spike height by 30% Application of tolbutamide likewise depolarized the alpha-cell (approximately 17 mV) and reduced action potential amplitude (43%). Whereas insulin secretion increased monotonically with increasing external K+ concentrations (threshold 25 mmol/l), glucagon secretion was paradoxically suppressed at intermediate concentrations (5.6-15 mmol/l), and stimulation was first detectable at >25 mmol/l K+. In alpha-cells isolated from SUR1-/- mice, both tolbutamide and glucose failed to produce membrane depolarization. These effects correlated with the presence of a small (0.13 nS) sulfonylurea-sensitive conductance in wild-type but not in SUR1-/- alpha-cells. Recordings of the free cytoplasmic Ca2+ concentration ([Ca2+]i) revealed that, whereas glucose lowered [Ca2+]i to the same extent as application of tolbutamide, the Na+ channel blocker tetrodotoxin, or the Ca2+ channel blocker Co2+ in wild-type alpha-cells, the sugar was far less effective on [Ca2+]i in SUR1-/- alpha-cells. We conclude that the KATP channel is involved in the control of glucagon secretion by regulating the membrane potential in the alpha-cell in a way reminiscent of that previously documented in insulin-releasing beta-cells. However, because alpha-cells possess a different complement of voltage-gated ion channels involved in action potential generation than the beta-cell, moderate membrane depolarization in alpha-cells is associated with reduced rather than increased electrical activity and secretion.